Unveiling the Invisible: Power, Inequality, and the Dynamics of Social Stratification - Dr. Bilal Butt (Research Journal of Psychology, 2023)
Social stratification, the hierarchical organization of societies based on power, privilege, and access to resources, is not a static reality. It is a dynamic system, fueled by invisible forces of power and inequality that shape individual life chances and collective destinies. This article delves into the complex mechanisms of social stratification, examining how systems of power, socioeconomic disparities, and cultural ideologies perpetuate unequal outcomes and maintain the status quo.